2007
DOI: 10.5194/angeo-25-2229-2007
|View full text |Cite
|
Sign up to set email alerts
|

Geotail observations of two-component protons in the midnight plasma sheet

Abstract: Abstract. Through the effort to obtain clues toward understanding of transport of cold plasma in the nearEarth magnetotail under northward IMF, we find that twocomponent protons are observed in the midnight plasma sheet (−10>X GSM >−30 R E , |Y GSM |<10 R E ) under northward IMF by the Geotail spacecraft. Since the twocomponent protons are frequently observed on the duskside during northward IMF intervals but hardly on the dawnside, those found in the midnight plasma sheet are thought to come from the dusk fla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 28 publications
2
17
0
Order By: Relevance
“…While our simulation does compare favorably with the qualitative asymmetry observed in nature, it is not our expectation that this idealized model should quantitatively reproduce any specific event. For instance, Nishino et al (), using a selection of several Geotail events, find the emergence of two‐component protons near midnight typically within 3 after the arrival of strongly northward IMF. As seen in Figure , relatively few flank‐entering particles are within ±10 R E of midnight after 3 hr of test particle integration.…”
Section: Resultsmentioning
confidence: 99%
“…While our simulation does compare favorably with the qualitative asymmetry observed in nature, it is not our expectation that this idealized model should quantitatively reproduce any specific event. For instance, Nishino et al (), using a selection of several Geotail events, find the emergence of two‐component protons near midnight typically within 3 after the arrival of strongly northward IMF. As seen in Figure , relatively few flank‐entering particles are within ±10 R E of midnight after 3 hr of test particle integration.…”
Section: Resultsmentioning
confidence: 99%
“…[34] While the cold electrons in the magnetotail plasma sheet have not been well studied, the presence of a cold component of ions in the magnetotail plasma sheet has been well established [e.g., Terasawa et al, 1997;Fujimoto et al, 1998;Øieroset et al, 2005;Wing et al, 2005;Nishino et al, 2007b]. Cold ions are more often observed under northward IMF than southward IMF [Øieroset et al, 2005;Wing et al, 2005], to the extent that a separate cold component is almost exclusively observed under northward IMF [Nishino et al, 2007b[Nishino et al, , 2007c. Transport through the flank magnetopause, perhaps via reconnection in rolled-up Kelvin-Helmholtz vortices [Hasegawa et al, 2004], is thought to be responsible for the presence of cold ions in the magnetotail under northward IMF.…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneous observations of Kelvin-Helmholtz vortices on both flanks are rare, and as such it is difficult to address any dawn-dusk asymmetry in their properties. However, Nishino et al (2011) reported one observation of vortices occurring simultaneously on both flanks and showed that while their macroscopic properties were similar, on a microscopic level differences were observed, with more plasma mixing between magnetosheath and magnetospheric populations in the dawnside vortex than the duskside vortex. Gradient drift entry naturally provides a dawn-dusk asymmetry: ions drift into the magnetosphere through the magnetopause on the dawn side, while electrons enter on the duskside (Olson and Pfitzer, 1985).…”
Section: Magnetopause Asymmetriesmentioning
confidence: 99%